A STUDY ON JOB SATISFACTION OF BANK EMPLOYEES WITH SPECIAL REFERENCE TO PERINTHALMANNA MUNICIPALITY,MALAPPURAM DISTRICT . - Fasla N.P (International Journal of Research Science and Management, 2017)
In this era of competitive world, success of any organization depends on its human resource. Banks are no exception to this. The employees of the bank valuable assets to the organization. In modern society the needs and requirements of the people are ever increasing and ever changing. When the people are ever increasing and ever changing and the people needs are not fulfilled they become dissatisfied. Dissatisfied people are likely to contribute very little for any purpose. Employees of the day expectt not a mere decent living but also a satisfied life. Due to change of technology, new rules and our social values, organizations have to face challenges. All the components affect the employee’s behaviours, attitudes and working situation. The work place is a second home for employees because they survive more than 40 hours a week in the working environment.